Large mode volume integrated Brillouin lasers for scalable ultra-low linewidth and high power - Kaikai Liu; Karl D. Nelson; Ryan O. Behunin; Daniel J. Blumenthal (Nature Communications)
Abstract Ultra-low linewidth, high output power, integrated single mode lasers, that operate from the visible to shortwave-IR, are critical for future compact, portable, precision applications. Achieving this performance in a CMOS compatible integration platform that can also enable scaling to lower linewidths and higher powers remains a key challenge. We report demonstration of a class of integrated laser with a 31 mHz instantaneous linewidth, 41 mW output power, and 73 dB sidemode suppression ratio, tunable over 22.5 nm. This performance is possible due to Brillouin nonlinear laser dynamics in a large mode volume, meter-scale, MHz free spectral range, low loss silicon nitride coil resonator with the potential to scale to an operating regime of mHz fundamental linewidth and Watt class lasers. Such lasers hold promise to unlock new sensitivity and fidelity for quantum sensing and computing, ultra-low-noise mmWave and RF generation, fiber sensing, and atomic, molecular, and optical physics.